Biocatalysis in Organic Media: Parameters Influencing Activity, Stability and Enantioselectivity - Costes, David (2001)
Biocatalysis in organic media offers very attractive methods to prepare fine chemicals. The biocatalyst performance regarding activity, stability and enantioselectivity will determine the viability of the bio-process. Therefore, the understanding and optimization of the parameters influencing enzyme performance in organic solvents are extremely important. In this thesis, reactions catalysed by hydroxynitrile lyases (HNLs) and lipases were studied. HNLs are well-established biocatalysts used for the enantioselective addition of hydrogen cyanide to carbonyl compounds. The interest for this enzymatic process is great since the enantiopure cyanohydrins prepared are potential intermediates for the asymmetric synthesis of pharmaceuticals and fine chemicals. HNLs from the following sources were used: Hevea brasiliensis, Manihot esculenta, Sorghum bicolor and Prunus amygdalus. The enantioselectivity was dependent of the HNL used but was not affected by the solvent hydrophobicity. Decreasing the temperature could increase enantioselectivity. The activity increased with increasing solvent hydrophobicity. However, too hydrophobic solvents provoke loss of activity. In fact, the choice of solvent was determined by the substrate concentration. At high substrate concentration, less hydrophobic solvents are required in order to achieve optimum activity. Lipases from different sources (Candida antarctica B, Rhizomucor miehei, Candida rugosa, Pseudomonas sp., and Rhizopus oryzae) were used for the resolution of secondary alcohols and acids, as well as for the preparation of a wax ester. The enantioselectivity of all the reactions studied varied with temperature. This variation can be explained by a simple thermodynamic relationship. On the other hand, the influence of solvent and water content on enantioselectivity is more unpredictable since it involves more than one mechanism.